2021
DOI: 10.12998/wjcc.v9.i26.7738
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of the nursing work environment on the work-family conflict in operating room nurses

Abstract: BACKGROUND The nursing working environment is an important subsystem in the hospital environment. A good working environment could have a positive impact on nurses. However, the work-family conflict and unsatisfactory working environment could significantly reduce their working enthusiasm, efficacy as well as the overall quality of the nursing, increase their fatigue, and thereby compromise their career status. AIM To explore the possible status quo and to analyze the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The professional status was presented in order of increasing hierarchical level: assistant nurse, nurse, surgery nurse, health executive, health senior executive and health director. Surgery nurses were analysed separately as their work conditions were different from other nurses (Fu et al, 2021). The last group, physicians, was included as index group to compare the present results with those of our previous studies carried out in physicians (Duba, Messiaen, Boulangeat, Boucekine, et al, 2020; Duba, Messiaen, Boulangeat, Korchia, et al, 2020; Duba, Messiaen, Masson, Lançon, et al, 2020; Messiaen et al, 2020, 2021).…”
Section: Population and Methodsmentioning
confidence: 99%
“…The professional status was presented in order of increasing hierarchical level: assistant nurse, nurse, surgery nurse, health executive, health senior executive and health director. Surgery nurses were analysed separately as their work conditions were different from other nurses (Fu et al, 2021). The last group, physicians, was included as index group to compare the present results with those of our previous studies carried out in physicians (Duba, Messiaen, Boulangeat, Boucekine, et al, 2020; Duba, Messiaen, Boulangeat, Korchia, et al, 2020; Duba, Messiaen, Masson, Lançon, et al, 2020; Messiaen et al, 2020, 2021).…”
Section: Population and Methodsmentioning
confidence: 99%
“…31 To a certain extent, the conflict between work and family can reduce their efficiency, enthusiasm, and service quality and increase their fatigue. 32 However, the impacts of shift work on nurse fatigue and work-family conflicts, especially among Chinese nurses in intensive care units, are not well understood.…”
Section: Shift Work Interferes With Sleep Rhythms and Causes Sleep Fr...mentioning
confidence: 99%
“…Several studies have demonstrated that work–family conflict significantly impacts shift workers' fatigue levels, such as ferry shipping employees 30 and married male physicians 31 . To a certain extent, the conflict between work and family can reduce their efficiency, enthusiasm, and service quality and increase their fatigue 32 . However, the impacts of shift work on nurse fatigue and work–family conflicts, especially among Chinese nurses in intensive care units, are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Tese items tackle leadership support to IPC, accountability of healthcare workers, and the efects of high workload and inadequate time on IPC practices. Tis factor generates an insight that nurses' working environment infuences the nurses' provision of efcient nursing service and efective IPC initiatives [33,34]. During the pandemic, nurses rendered most of their time to patient care, often facing a higher patient load that demands attention [35].…”
Section: Discussionmentioning
confidence: 99%